A Study on Soil Thermophilic and Thermotolerant Fungi in Thamar-Yemen - Al-Bader, Salah M; Aleryani , Adel Q; Almutaa, Aisha A. (Journal of agricultural, environmental and veterinary sciences, 2017)
Thirty-eight soil samples were collected from different sites in Thamar province during the period from 4/2012 to 2/2013.The direct plate, and dilution plates methods were followed to isolation of counting colony forming units, the potato carrot agar (PCA) and Emerson’s media were used A total of 23 fungi belong to (14) genera were isolated, they include (11) Hyphomycetes, (10) Ascomycetes, and (2) Zygomycetes besides black and white sterile mycelium. A fourteen isolates were regarded asnewly record for Yemeni mycobiota,they include Acremonium murorum, Acrophialophorafusispora, Chaetomiumatrobrunneum, C.gracile,C.strumarium, C.therophilevar.coprophpile, Corynascussepedonium ,Emericellarugulosa, Melanocarpusalbomyces, paecelomycesinflatus Papulosporathermophila, Rhizomucormiehi, Scytalidiumthermophilum, and Talromycesthermophilus Soil dilution method showed that the colony forming units (CFUs)in soil had seasonal fluctuation , they were significantly higher (36667) during moderate/humid month than cold/dry months (20400) (p<0.05), while the total similarity% is high between fungal genera which were isolated during the two periods (78.57%) .A test of 15 isolates to produce cellulase, amylase, lipase, protease, xylanase and phenoloxidase showed a different activities in number of enzymes and levels of production. Corynascussepedonium, Eemericellanedulans and Malbrancheacinnamomea gave a positive result for all enzymes